If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(10 + 7x) = 7(4x + 3) (10 * 7 + 7x * 7) = 7(4x + 3) (70 + 49x) = 7(4x + 3) Reorder the terms: 70 + 49x = 7(3 + 4x) 70 + 49x = (3 * 7 + 4x * 7) 70 + 49x = (21 + 28x) Solving 70 + 49x = 21 + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 70 + 49x + -28x = 21 + 28x + -28x Combine like terms: 49x + -28x = 21x 70 + 21x = 21 + 28x + -28x Combine like terms: 28x + -28x = 0 70 + 21x = 21 + 0 70 + 21x = 21 Add '-70' to each side of the equation. 70 + -70 + 21x = 21 + -70 Combine like terms: 70 + -70 = 0 0 + 21x = 21 + -70 21x = 21 + -70 Combine like terms: 21 + -70 = -49 21x = -49 Divide each side by '21'. x = -2.333333333 Simplifying x = -2.333333333
| xy+3y=8x-20 | | 2x=10-3y | | 8v^2+16v-64=0 | | 23x+12=21x+34 | | (-0.4-2)+1.3= | | x/6=7.68 | | 6u+8v-7(6u-4v+8w)= | | 6x=5x+2(x-1)-x+3 | | 3.14*4*2.25/3= | | 310/2.0=333/X | | 3.14*4= | | -5(2x-3)= | | 3(5x+4)=9 | | xy+3y=8y-20 | | x^3-17x^2+90x-140=0 | | 4a-3a=20 | | 7f-15=f+3 | | -16x^2+8t+8=0 | | 15x+19y=4 | | 7(q-4)+3(q-5)=-23 | | 3x*x+5-2x-1= | | 19x+15y=3 | | y+9=5(x+10) | | 3xsquared+5-2x-1= | | n-26=(-13) | | 8(3x-3y)-4(8x+3y)= | | 6e+7=2e+11 | | y=1.05e+15 | | 9x+9=6-(8x-4) | | 39x=64x+24 | | 10x+12+4x-3= | | 5y-6+y+53=8y+50-5y |